Assessment of Fibre Characteristics and Suitability of Sida acuta Burm F. for Pulp and Paper Production - O Ajala, Olayiwola; Adebawo, Funke G; Adegoke, Olaoluwa A.; Amoo-Onidundu, Oladele (International Journal of Engineering and Management Sciences, 2025)
The ever-increasing demand for paper and paper products and alarming rate of global population growth necessitates research into non-wood fibre to augment the popular wood fibres in short supply. Sida acuta obtained at two locations, samples collected from 3 areas per location. Samples of dimension 10 x 10 x 20 mm macerated in equal volumes of glacial acetic acid and 30% hydrogen peroxide at 80oC in an oven. Twenty-five whole fibres in swollen condition were measured. Derivatives of fibre dimensions viz: Runkel ratio, flexibility and slenderness were also evaluated. Pooled mean fibre length was 1.04mm, pooled fibre diameter was 25.02μm, pooled fibre lumen width was 14.69μm and fibre cell wall thickness was 5.17μm. Runkel ratio was 0.73, coefficient of suppleness (flexibility) was 60.05 while felting power (slenderness) was 42. Values obtained connote that S. acuta’s fibre morphology is good for pulping much more that its Runkel ratio (0.73) is less than 1, coefficient of suppleness (60.05) is greater than 50 and its felting power (42) is greater than 33. Specific Gravity ranged from 0.416–0.468. With reference to the above, S. acuta is fairly suitable for pulp and paper making.